2022
DOI: 10.1002/jbt.23188
|View full text |Cite
|
Sign up to set email alerts
|

Moronic acid improves intestinal inflammation in mice with chronic colitis by inhibiting intestinal macrophage polarization

Abstract: This study focuses on exploring the role and mechanism of moronic acid (MOA), a small triterpenoid molecule, against inflammatory bowel disease (IBD). Intestinal macrophages were cultured in vitro, and their M1 polarization was induced by lipopolysaccharide (LPS) and interferon gamma (IFN‐γ). After intervention with MOA, the proportion of M1 macrophages was detected, and the levels of inflammatory cytokines (TNF‐α, IL‐6, and IL‐1β) were examined by ELISA. IFA staining was performed to determine the P50 and CD8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Although not yet fully understood, several studies have demonstrated that pentacyclic triterpenes can induce cell death by apoptosis (Chudzik et al, 2015 ; Coricovac et al, 2021 ; Hodoň et al, 2022 ; Mioc et al, 2022 ; Oprean et al, 2018 ; Ren & Kinghorn, 2019 ) or autophagy (El-Baba et al, 2021 ; Fogde et al, 2022 ; Wang et al, 2022b ). Also, moronic acid was shown to have cytotoxic properties (Rios et al, 2001 ) as well as other beneficial effects such as anti-viral (Chang et al, 2010 ; Yu et al, 2006 ), anti-inflammatory (Ruan & Zha, 2022 ) and anti-diabetic activity (Cerón-Romero et al, 2016 ; Estrada-Soto et al, 2022 ; Ramírez-Espinosa et al, 2013 ), indicating the potential of triterpenoic acids and the necessity of further studies for the investigation of their biological properties.…”
Section: Resultsmentioning
confidence: 99%
“…Although not yet fully understood, several studies have demonstrated that pentacyclic triterpenes can induce cell death by apoptosis (Chudzik et al, 2015 ; Coricovac et al, 2021 ; Hodoň et al, 2022 ; Mioc et al, 2022 ; Oprean et al, 2018 ; Ren & Kinghorn, 2019 ) or autophagy (El-Baba et al, 2021 ; Fogde et al, 2022 ; Wang et al, 2022b ). Also, moronic acid was shown to have cytotoxic properties (Rios et al, 2001 ) as well as other beneficial effects such as anti-viral (Chang et al, 2010 ; Yu et al, 2006 ), anti-inflammatory (Ruan & Zha, 2022 ) and anti-diabetic activity (Cerón-Romero et al, 2016 ; Estrada-Soto et al, 2022 ; Ramírez-Espinosa et al, 2013 ), indicating the potential of triterpenoic acids and the necessity of further studies for the investigation of their biological properties.…”
Section: Resultsmentioning
confidence: 99%
“…In an in vitro and in vivo study using IFN-γ-stimulated intestinal macrophages and DSS-induced C57BL/6 mice model of colitis, respectively, Ruan and Zha [ 35 ] assessed the roles of moronic acid against a triterpenoid richly found in Pistacia chinensis , against NLRP3 activation during IBD. The results showed that with treatment, the cells expressed decreased TNF-α, IL-1β, IL-6, ROS, CD11, NF-kB (P50), NLRP3, p-P50, and M1 macrophage polarization.…”
Section: Ibd Nlrp3 Inflammasome and Implications Of Plant-derived Int...mentioning
confidence: 99%